The history of the Galactic bulge - Zijlstra, A. A. (2016)
Planetary nebulae form in stellar populations with ages from 1 to 10 Gyr, and can be used to trace their star formation histories. Here we apply this to the Galactic bulge, where there are indications both for an old origin and for younger stars. We use new stellar models, which have significant different evolutionary speeds during the post-AGB phase. We apply these new models to a sample of 32 planetary nebulae with HST imaging and VLT spectroscopy. The results show evidence for an old starburst, followed by continuous star formation until at least 2Gyr ago. This agrees very well with recent analysis of colour-magnitude diagrams of the bulge. We show that the new models can also explain the [OIII] luminosity functions, and predict the uniform luminosity cut-off both in spiral galaxies and old elliptical galaxies.